Technologies for the functionalization of textile mats with nanoparticles - Visileanu, Emilia (Array, 2019)
Nanotechnology is the science of materials with extremely small dimensions (one nanometer is one billionth meter), but it is a major developing industry with an estimated annual market of about one trillion US dollars by 2017[1]. Nanoparticles are used or evaluated for use in many areas, which is currently demonstrated on the market for over 1,000 nano-products. The impact of nanotechnology extends from its medical, ethical, mental, legal and environmental applications to areas such as engineering, biology, chemistry, computer science, materials science and communications [2-3]. Potential risks include environmental, health and safety issues; transient effects, such as the reallocation of traditional industries as nanotechnology products, are becoming dominant and are a cause for concern for privacy lawyers [4-5]. Textile of 100% cotton, 55% polyester / 45% cotton and 100% polyester, white and dyed, were functionalized by spraying technology on a test device made at UT Dresden after oleofobization with Rucostar EEF6 or Nuva N 2114 and impregnation by applying oleophobic treatment simultaneously with the functionalization with Ag NP. Analysis of the size and form of Ag NP was achieved by using SEM electronic microscopy, TEM and dynamic light scattering (DLS) transmission microscopy. The uniformity, dispersion and migration of Ag NP from the surface of the textile materials for the initial samples compared with those tested for acid / alkaline perspiration, washing and wear (rubbing) revealed by AAS determinations that the acidic sweat test is the most aggressive leading to decreases in the amount of Ag NP of approx. 25% versus untreated sample.The amount of Ag NP deposited on the textile by the two technologies did not differ significantly.